2009
DOI: 10.1007/s00264-009-0805-2
|View full text |Cite
|
Sign up to set email alerts
|

Coccygectomy with or without periosteal resection

Abstract: The purpose of this study was to compare the clinical outcomes and wound complications in coccygectomy with or without subperiosteal resection. This retrospective study included 25 patients who underwent coccygectomy. Resection of all mobile coccygeal segments including the periosteum was performed in 11 patients (group 1) and resection was performed subperiostally sparing the periosteum in the remaining 14 patients (group 2). A visual analogue scale was used for pain assessment before and after the surgery bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
1
10

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(78 citation statements)
references
References 23 publications
1
66
1
10
Order By: Relevance
“…We are not experienced with a recently introduced subperiosteal technique [14], which anyway may be of interest, since it was published by the end of our study. Success rate in coccygectomy range from 100 to 54 % [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are not experienced with a recently introduced subperiosteal technique [14], which anyway may be of interest, since it was published by the end of our study. Success rate in coccygectomy range from 100 to 54 % [17].…”
Section: Discussionmentioning
confidence: 99%
“…Adhesive sterile drapes were placed on site after skin disinfection. We performed coccygectomy following Key's technique [10], as thoroughly described by Bilgic et al [14] in their Group 1 patients. We never used sub-periosteal technique [14].…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Trauma may be acute from a fall or during childbirth, or chronic and repetitive, when obesity may be a predisposing factor [2,7]. Less common causes of coccydynia may be due to local bone or soft tissue pathology [8][9][10]. However, one-third of cases are idiopathic [2,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Less common causes of coccydynia may be due to local bone or soft tissue pathology [8][9][10]. However, one-third of cases are idiopathic [2,[9][10][11]. Some authors have suggested that individuals with a greater ventral angulation of the coccyx are more at risk of developing idiopathic coccydynia [3,12].…”
Section: Introductionmentioning
confidence: 99%